PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Li, Jia; Lu, Xi; Wei, Liqing; Ye, Dan; Lin, Jianqiang; Tang, Xiaoyu; Cui, Kaixuan; Yu, Shanshan; Xu, Yue; Liang, Xiaoling (Inflammation research, 2022)
Objective Diabetic macular edema (DME) is one of the most frequent causes of severe vision loss. The pathogenesis of DME is still not fully understood; however, it is hypothesized to result from breakdown of the blood–retinal barrier (BRB) due to retinal inflammation by vascular endothelial growth factor (VEGF) secretion under hyperglycemic conditions. In this investigation, we discovered that Prolyl-4-hydroxylase 2 (PHD2), an upstream regulator of hypoxia-inducible factor 1 (HIF-1) modulates VEGF expression and thus preserves BRB function in the mouse retina. Materials and methods Primary human retinal microvascular endothelial cells (hRMECs) were cultured in human endothelial serum-free growth medium and exposed to hyperglycemia. Changes in cell viability were investigated by an MTT assay. BRB function in each group was revealed by a paracellular permeability assay and trans-endothelial electrical resistance (TEER). Morphological changes in the BRB were investigated by immunofluorescence staining of occludin and zonula occludens-1 (ZO-1). The mRNA and protein levels of the tight junction proteins, PHD2, HIF-1α, and VEGF were measured by reverse transcription-quantitative PCR (RT-qPCR), western blot analysis and ELISA. Results Under hyperglycemic conditions, the viability of hRMECs was decreased, and PHD2 expression was downregulated, accompanied by increased paracellular permeability and decreased trans-endothelial electrical resistance. Additionally, HIF-1α and VEGF expression levels were increased, whereas the expression levels of tight junction proteins, including occludin and ZO-1, were decreased and BRB function was compromised. The PHD2 activator R59949 (diacylglycerol kinase inhibitor II), altered these pathological changes, and the PHD2 inhibitor dimethyloxalylglycine (DMOG) resulted in the opposite effects. Conclusion These results demonstrated that PHD2 inhibited HIF-1 activity by inhibiting HIF-1α expression in hRMECs under hyperglycemic conditions, which led to the downregulation of the expression of the angiogenic factor VEGF, and thus helped to maintain the functions of hRMECs. Therefore, it is reasonable to propose that PHD2 could be a potential novel target for the treatment of DME or other diseases with a similar pathogenesis.